Evaluasi Sistem Informasi Industri Konstruksi menggunakan COBIT - Budi Setyawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Kwan Setia Construction is a company engaged in the construction industry. This company has been around for a long time and has used information systems to support the company's operations. In an effort to support the company's operations, the system and application must not stop serving the company's operations. If there is a problem with the system, the company's vision and mission will not be achieved. Therefore, the existing information system needs to be evaluated, considering that the system has served operations starting from the process of getting customers, the construction process, the inventory system to the financial system. Management currently intends to measure or evaluate all construction information system services. In evaluating the construction information system using the COBIT 5 framework. The goal of the construction company is to target the maturity level at level 3, where currently the company still has maturity at level 2. Changes will be made to increase the maturity level.